Bond role in strut-and-tie systems modelling reinforced-concrete members. (15th April 2020) - Bamonte, Patrick; Gambarova, Pietro G.; Invernizzi, Raul
Highlights: Roles of microcracked and solid concrete in the bonding of long anchored bars and ties. Clear subdivision between stress transfer by interlock and by adhesion in bonded ties. Direct introduction of bond in strut-and-tie systems. Rational identification of the position of bond-related joints in strut-and-tie systems, to improve safety checks. Simple model to investigate the roles of stirrups and rebars in anchored ties in RC. Abstract: The unknown a priori position of bond-related joints in the strut-and-tie systems used in reinforced-concrete modelling is determined in this paper by developing a simple model concerning a single stiff and strong deformed bar (tie), that is embedded in a reinforced concrete member. The model takes into account the bonded length, the bond-stress profile and the nature of the bond along the tie (basically by interlock due to the formation of microcracks and microstruts, as well as by adhesion ). The interaction between the position of the joint and the yielding of the reinforcement around the bonded tie, as well as the shares of the pull-out force resisted by interlock and by adhesion, are dealt with in detail, in order to maximize the bearing capacity of the tie within the static approach to limit analysis. Any tie, like those found in the strut-and-tie systems used in representing 2D regions, can be treated in accordance with the proposed model, provided that no direct confinement be applied by the supports or by the loads. The model may be a useful tool to evaluate the bearing capacity of reinforced-concrete structural systems.